Recommendations on terminology and experimental best practice associated with plant nitric oxide research - Gupta, Kapuganti Jagadis; Hancock, John T; Petrivalsky, Marek; Kolbert, Zsuzsanna; Lindermayr, Christian; Durner, Jorg; Barroso, Juan B; Palma, José M; Brouquisse, Renaud; Wendehenne, David; Corpas, Francisco J; Loake, Gary J (The New phytologist, 2020)
Nitric oxide (NO) emerged as a key signal molecule in plants. During the last two decades impressive progress has been made in plant NO research. This small, redox-active molecule is now known to play an important role in plant immunity, stress responses, environmental interactions, plant growth and development. To more accurately and robustly establish the full spectrum of NO bioactivity in plants, it will be essential to apply methodological best practice. In addition, there are some instances of conflicting nomenclature within the field, which would benefit from standardization. In this context, we attempt to provide some helpful guidance for best practice associated with NO research and also suggestions for the cognate terminology.
Keywords: nitric oxide synthase; mitochondria; rostliny; S-nitrosylation; vývoj rostlin; oxid dusnatý; Plant Development; fluorescence; nitric oxide; Nitric Oxide; Plants; nitrate reductase